Sex differences in opioid response: a role for the gut microbiome? - Han, Caitlin; Manners, Melissa T.; Robinson, Shivon A. (Frontiers in Pharmacology, 2024)
Opioid drugs have been long known to induce different responses in males compared to females, however, the molecular mechanisms underlying these effects are yet to be fully characterized. Recent studies have established a link between the gut microbiome and behavioral responses to opioids. Chronic opioid use is associated with gut dysbiosis, or microbiome disruptions, which is thought to contribute to altered opioid analgesia and reward processing. Gut microbiome composition and functioning have also been demonstrated to be influenced by sex hormones. Despite this, there is currently very little work investigating whether sex differences in the gut microbiome mediate sex-dependent responses to opioids, highlighting a critical gap in the literature. Here, we briefly review the supporting evidence implicating a potential role for the gut microbiome in regulating sexually dimorphic opioid response and identify areas for future research.